Faktor-faktor pengaruh minat nasabah pengguna internet banking Bank Syariah Mandiri - M. Rifki Bakhtiar; Erawati Kartika; Ika Listyawati (Universitas Darussalam Gontor, 2020)
This study aims to analyze and obtain evidence of the factors that influence the interest in using internet banking. The object of this research is BSM (Bank Syariah Mandiri) customers who use internet banking. The research data is in the form of primary data with data collection using a questionnaire with a purposive sampling method. The data analysis method used is multiple linear regression. The results showed that trust, security, ease of use, and service features had a positive and significant effect on the interest in using internet banking. The results of this study are expected to contribute to BSM (Bank Syariah Mandiri) in formulating its marketing strategy in order to maintain a competitive internet banking and develop a system of internet banking in the future so that BSM customers (Bank Syariah Mandiri) can continue to use internet banking.